Structural stability and Sin a 1 anti-epitope antibody binding ability of yellow mustard (Sinapis alba L.) napin during industrial-scale myrosinase inactivation process. Issue 7 (8th July 2015) - Marambe, Harsha K.; McIntosh, Tara C.; Cheng, Bifang; Wanasundara, Janitha P.D.
<x xml:space="preserve">Abstract</x> Industrial-level myrosinase inactivation maintains the key structural features of Sin a 1 napin but improves the gastrointestinal enzymatic susceptibility of its allergenic epitope.